Electrospinning carbon nanofiber material prepared from PILs-PAN mixed precursor and application of electrospinning carbon nanofiber material in vanadium battery

The preparation of electrospun carbon nanofiber materials through PILs-PAN hybrid precursors solves the problem of insufficient electrochemical reaction activity of existing vanadium battery electrode materials, improves the electrode reaction area and energy conversion efficiency, and promotes the improvement of vanadium battery performance .

CN119243374AActive Publication Date: 2025-01-03LIAONING UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411401317.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-01-03
Estimated Expiration
2044-10-09

AI Technical Summary

Technical Problem

The existing vanadium battery electrode materials are based on polyacrylonitrile-based carbon fibers, and have poor electrochemical reaction activity, which limits the performance and industrial development of vanadium batteries.

Method used

Binary nanofiber materials are prepared by electrospinning technology by electrospinning technology, and electrospinned carbon nanofiber materials with gradient pore structure are formed to enhance electrode activity.

Benefits of technology

It significantly improves the electrode reaction area and reaction activity, improves the battery's energy conversion efficiency and electrolyte utilization rate, and improves the performance of vanadium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119243374A_ABST
    Figure CN119243374A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of battery materials and energy storage, in particular to an electrospinning carbon nanofiber material prepared from a PILs-PAN mixed precursor and application of the electrospinning carbon nanofiber material in a vanadium battery. The preparation method comprises the following steps: preparing a PILs-PAN mixed precursor into a binary nanofiber material in which polymeric ionic liquid PILs fine fibers are uniformly distributed on the surface of polyacrylonitrile PAN crude fibers through an electrostatic spinning technology, and then carrying out pre-oxidation treatment and carbonization treatment to obtain the electrospun carbon nanofiber material with a gradient pore structure. According to the preparation method, the carbon nanofibers with different diameters can be obtained by simply changing the composition of the precursor solution by utilizing a simple and controllable electrostatic spinning technology, namely introducing the polymeric ionic liquid with high conductivity; the fine fibers with the diameter of dozens of nanometers are attached to the surfaces of the PAN fibers with the diameter of hundreds of nanometers, so that the reaction area and the reaction activity of the electrode are effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of battery materials and energy storage, and in particular to an electrospun carbon nanofiber material prepared from a PILs-PAN mixed precursor and application thereof in a vanadium battery. Background Art

[0002] The development of clean and renewable energy is a key way to solve the crisis of fossil fuels such as oil, and has become a core strategy to ensure energy security, improve the ecological environment, and promote green and sustainable development. With the rapid development of renewable energy, the matching large-scale energy storage technology has gradually become a research hotspot. Among the many energy storage technologies, redox flow batteries have gradually become the leader in the field of large-scale and long-term energy storage with their inherent safety, scalability, long cycle life, fast response speed and large energy storage capacity.

[0003] Electrodes are the place where electrochemical reactions of vanadium batteries occur, and their performance directly determines the energy conversion efficiency and stability of the battery. At present, the electrode materials widely used in the market are mainly based on polyacrylonitrile-based carbon fibers, which have the advantages of low cost, high conductivity and good chemical stability, but their electrochemical reaction activity is poor, which seriously limits their application performance and the industrial development of vanadium batteries. Summary of the invention

[0004] In view of the above-mentioned technical problems, the purpose of the present invention is to provide an electrospun carbon nanofiber material prepared from a PILs-PAN mixed precursor, and apply it to the electrode material of all-vanadium liquid flow battery, which can effectively improve the electrode activity and enhance the battery performance.

[0005] To achieve the above-mentioned purpose of the invention, the technical solution adopted by the present invention is: an electrospun carbon nanofiber material prepared from a PILs-PAN mixed precursor, wherein the PILs-PAN mixed precursor is first subjected to electrospinning technology to prepare a binary nanofiber material, and then subjected to pre-oxidation treatment and carbonization treatment to obtain an electrospun carbon nanofiber material with a gradient pore structure; the binary nanofiber material is composed of fine fibers of polymerized ionic liquid PILs uniformly distributed on the surface of coarse fibers of polyacrylonitrile PAN.

[0006] Furthermore, the diameter of the polymerized ionic liquid (PILs) fine fiber is 10 to 30 nm, and the diameter of the polyacrylonitrile (PAN) coarse fiber is 100 to 300 nm.

[0007] Furthermore, the polymeric ionic liquids (PILs) are polymeric ionic liquids PILs prepared using 1-vinyl-3-methylimidazole as a monomer.

[0008] Furthermore, the molecular weight of the polyacrylonitrile (PAN) is 90,000 to 150,000.

[0009] A method for preparing an electrospun carbon nanofiber material prepared from a PILs-PAN mixed precursor comprises the following steps:

[0010] 1) dissolving polyacrylonitrile (PAN) in a N,N,-dimethylformamide (DMF) solution to obtain a PAN / DMF electrospinning precursor solution having a PAN mass percentage concentration of 10 to 20%;

[0011] 2) Using 1-vinyl-3-methylimidazole as a monomer, polymeric ionic liquids (PILs) were prepared;

[0012] 3) adding polymerized ionic liquids (PILs) to the PAN / DMF electrospinning precursor solution prepared in step 1), mixing them evenly to prepare a PILs-PAN / DMF mixed precursor solution;

[0013] 4) The PILs-PAN / DMF mixed precursor solution is sucked into an electrospinning syringe, and electrospinning is performed using an electrospinning technique to prepare a binary nanofiber material in which polymerized ionic liquid PILs fine fibers are uniformly distributed on the surface of polyacrylonitrile PAN coarse fibers;

[0014] 5) The binary nanofiber material is flattened with a corundum plate, placed in a tube furnace for pre-oxidation treatment and carbonization treatment, and then cooled to room temperature to obtain an electrospun carbon nanofiber material with a gradient pore structure.

[0015] Further, step 2) is specifically: 1-vinyl-3-methylimidazolium bromide (ViEtIm + Br - ) and azobisisobutyronitrile (AIBN) were added to CHCl3 solvent, and refluxed in an oil bath at 70℃~80℃ for 5~6h under N2 protective atmosphere. After cooling to room temperature, the obtained product was washed with CHCl3 and dried in vacuum to obtain polymeric ionic liquids (PILs).

[0016] Furthermore, in step 3), the mass ratio of polymerized ionic liquids (PILs) to PAN is 1:50 to 1:200.

[0017] Furthermore, in step 4), the process conditions of the electrospinning technology are as follows: the stainless steel nozzle model is G15~G22; the collector is a stainless steel roller, and the roller speed is 50~150r / min; the voltage between the nozzle and the roller is 18~22kV; the distance between the nozzle and the roller is 10~15cm; the spinning temperature is 25~30℃; the spinning humidity is 30~50%RH; the pushing speed is 10~50μL / min.

[0018] Furthermore, in step 5), the conditions for the pre-oxidation treatment are: in an air atmosphere, heating to 180-200°C at a heating rate of 2-5°C / min, keeping warm for 10-20 minutes, then heating to 290-300°C at a heating rate of 1-2°C / min, and keeping warm for 60-70 minutes; the conditions for the carbonization treatment are: in a nitrogen or argon atmosphere, heating to 1000-1100°C at a heating rate of 5-10°C / min, and keeping warm for 120-130 minutes.

[0019] The present invention provides an application of an electrospun carbon nanofiber material prepared from a PILs-PAN mixed precursor as an electrode material in an all-vanadium liquid flow battery.

[0020] The beneficial effects of the present invention are:

[0021] 1. The present invention utilizes simple and controllable electrospinning technology to obtain binary nanofibers with different diameters by simply changing the composition of the precursor solution, that is, introducing a polymerized ionic liquid with high conductivity; PILs fine fibers with a diameter of more than ten nanometers are attached to the surface of PAN fibers with a diameter of several hundred nanometers, effectively increasing the electrode reaction area and reaction activity.

[0022] 2. The present invention has a simple method and strong controllability, and can significantly improve the wettability of the electrode, and improve the electrolyte utilization rate and energy conversion efficiency during the battery charging and discharging process. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Scanning electron microscope images of PAN-ECNFs (a) and PILs-PAN-ECNFs (b) prepared in Example 1.

[0024] Figure 2 Cyclic voltammetry curves of PAN-ECNFs and PILs-PAN-ECNFs prepared in Example 1 in 0.1M VOSO4+2M H2SO4 (scan rate: 5mV·s -1 ). DETAILED DESCRIPTION

[0025] In order to better understand the above-mentioned technical scheme, the technical scheme of the embodiments of the present application is described in detail below through the accompanying drawings and specific embodiments. It should be understood that the embodiments of the present application and the specific features in the embodiments are detailed descriptions of the technical scheme of the embodiments of the present application, rather than limitations on the technical scheme of the present application. In the absence of conflict, the embodiments of the present application and the technical features in the embodiments may be combined with each other.

[0026] In a first aspect of an embodiment of the present invention, there is provided an electrospun carbon nanofiber material prepared from a PILs-PAN mixed precursor, wherein the PILs-PAN mixed precursor is first subjected to electrospinning technology to prepare a binary nanofiber material, and then subjected to pre-oxidation treatment and carbonization treatment to obtain an electrospun carbon nanofiber material with a gradient pore structure; the binary nanofiber material is composed of fine fibers of polymerized ionic liquid PILs uniformly distributed on the surface of coarse fibers of polyacrylonitrile PAN.

[0027] The present invention introduces high-conductivity polymerized ionic liquids (PILs) into the traditional PAN / DMF precursor solution by regulating the composition of the electrospinning precursor solution. After electrospinning, the polymerized ionic liquid (PILs) fine fibers are evenly distributed on the surface of the polyacrylonitrile (PAN) coarse fibers to form a binary nanofiber material, and then the electrospun carbon nanofiber material with a gradient pore structure is obtained after pre-oxidation and carbonization treatment, thereby effectively increasing the active reaction area of ​​the electrode. The surface activity and hydrophilicity of the electrode are significantly improved, which can effectively promote the electrode reaction process of the positive and negative electrodes of the vanadium battery and improve the energy conversion efficiency of the battery.

[0028] In some feasible embodiments, further, the diameter of the polymeric ionic liquid (PILs) fine fiber is 10 to 30 nm, and the diameter of the polyacrylonitrile (PAN) coarse fiber is 100 to 300 nm.

[0029] The polymerized ionic liquid (PILs) fine fibers and polyacrylonitrile (PAN) coarse fibers provided by the present invention are carbon nanofibers with different diameters. The PILs fine fibers with a diameter of more than ten nanometers are attached to the surface of PAN fibers with a diameter of several hundred nanometers to form a gradient pore structure. The small-diameter fibers provide a larger active area, which is beneficial to reducing electrochemical polarization. The large-diameter fibers provide a larger pore structure, which is beneficial to reducing concentration polarization. The reduction of polarization overpotential is more conducive to improving the electrolyte utilization rate and energy conversion efficiency of the battery, and effectively improving the electrode reaction area and reaction activity.

[0030] In some feasible embodiments, further, the polymeric ionic liquid (PILs) is a polymeric ionic liquid PILs prepared using 1-vinyl-3-methylimidazole as a monomer. The preparation of polymeric ionic liquid PILs using 1-vinyl-3-methylimidazole as a monomer has the advantages of low cost, simple method and high yield.

[0031] In some feasible embodiments, further, the molecular weight of the polyacrylonitrile (PAN) is 90,000 to 150,000, so as to obtain a PAN / DMF precursor solution with a suitable concentration and viscosity, which is conducive to the subsequent electrospinning.

[0032] A second aspect of an embodiment of the present invention provides a method for preparing an electrospun carbon nanofiber material prepared from a PILs-PAN mixed precursor, comprising the following steps:

[0033] 1) dissolving polyacrylonitrile (PAN) in a N,N,-dimethylformamide (DMF) solution to obtain a PAN / DMF electrospinning precursor solution having a PAN mass percentage concentration of 10 to 20%;

[0034] 2) Using 1-vinyl-3-methylimidazole as a monomer, polymeric ionic liquids (PILs) were prepared;

[0035] 3) adding polymerized ionic liquids (PILs) to the PAN / DMF electrospinning precursor solution prepared in step 1), mixing them evenly to prepare a PILs-PAN / DMF mixed precursor solution;

[0036] 4) The PILs-PAN / DMF mixed precursor solution is sucked into an electrospinning syringe, and electrospinning is performed using an electrospinning technique to prepare a binary nanofiber material in which polymerized ionic liquid PILs fine fibers are uniformly distributed on the surface of polyacrylonitrile PAN coarse fibers;

[0037] 5) The binary nanofiber material is flattened with a corundum plate, placed in a tube furnace for pre-oxidation treatment and carbonization treatment, and then cooled to room temperature to obtain an electrospun carbon nanofiber material with a gradient pore structure.

[0038] The present invention utilizes a simple and controllable electrospinning technology, and by simply changing the composition of a precursor solution, namely, introducing a polymerized ionic liquid with high electrical conductivity, a binary nanofiber material consisting of two different fiber diameters can be obtained through a one-step electrospinning process; fine fibers with a diameter of more than ten nanometers are attached to the surface of PAN fibers with a diameter of several hundred nanometers, and the binary nanofiber material is subjected to subsequent pre-oxidation and carbonization processes to finally obtain a porous carbon nanofiber electrode material, which effectively increases the electrode reaction area and the surface activity and hydrophilicity of the electrode are significantly improved, and can effectively promote the electrode reaction process of the positive and negative electrodes of the vanadium battery and improve the energy conversion efficiency of the battery.

[0039] In some feasible embodiments, further, step 2) is specifically: 1-vinyl-3-methylimidazolium bromide (ViEtIm + Br - ) and azobisisobutyronitrile (AIBN) were added to CHCl3 solvent, refluxed in an oil bath at 70°C to 80°C for 5 to 6 hours under a N2 protective atmosphere, and after cooling to room temperature, the resulting product was washed with CHCl3 and dried in vacuo to obtain polymeric ionic liquids (PILs).

[0040] In some feasible embodiments, further, in step 3), by mass ratio, polymerized ionic liquid (PILs):PAN=1:50~1:200; a suitable mass ratio of PILs to PAN can obtain a binary nanofiber material in which fine fibers of polymerized ionic liquid PILs are uniformly distributed on the surface of polyacrylonitrile PAN coarse fibers; if the amount of PILs is too small and the fine fibers are too few, the activity improvement effect of the prepared electrode material is not obvious; if the amount of PILs is too large and the fine fibers are too many, the porosity of the three-dimensional network structure of the carbon fibers is reduced, which is not conducive to the circulation of the electrolyte inside the electrode.

[0041] In some feasible embodiments, further, in step 4), the process conditions of the electrospinning technology are: the stainless steel nozzle model is G15-G22; the collector is a stainless steel roller, and the roller speed is 50-150r / min; the voltage between the nozzle and the roller is 18-22kV; the distance between the nozzle and the roller is 10-15cm; the spinning temperature is 25-30℃; the spinning humidity is 30-50%RH; the pushing speed is 10-50μL / min. Under these process parameters, electrospinning can obtain binary nanofiber materials with good uniformity and continuity.

[0042] In some feasible embodiments, further, in step 5), the conditions of the pre-oxidation treatment are: in an air atmosphere, heating to 180-200°C at a heating rate of 2-5°C / min, keeping warm for 10-20 minutes, then heating to 290-300°C at a heating rate of 1-2°C / min, and keeping warm for 60-70 minutes; the pre-oxidation treatment can maintain the structure of the PAN nanofibers during the subsequent high-temperature carbonization process; the conditions of the carbonization treatment are: in a nitrogen or argon atmosphere, heating to 1000-1100°C at a heating rate of 5-10°C / min and keeping warm for 120-130 minutes; the appropriate carbonization process allows graphite crystals to be generated in the fibers, giving them higher conductivity.

[0043] A third aspect of the embodiments of the present invention provides the use of an electrospun carbon nanofiber material prepared from a PILs-PAN mixed precursor as an electrode material in an all-vanadium liquid flow battery.

[0044] In summary, the present invention utilizes simple and controllable electrospinning technology to prepare porous carbon nanofibers by simply changing the composition of the precursor solution, which effectively increases the electrode reaction area and reaction activity, can significantly improve the wettability of the electrode, and improve the electrolyte utilization rate and energy conversion efficiency during the battery charging and discharging process.

[0045] Example 1

[0046] (I) Comparative example: polyacrylonitrile carbon nanofiber electrode material (PAN-ECNFs)

[0047] The preparation method comprises the following steps:

[0048] 1) Dried polyacrylonitrile (PAN) powder with a molecular weight of 150,000 was dissolved in N,N,-dimethylformamide (DMF) solution, and magnetically stirred at 80° C. for 6 h until completely dissolved, to obtain a PAN / DMF electrospinning precursor solution with a polyacrylonitrile (PAN) mass percentage concentration of 14%.

[0049] 2) The PAN / DMF electrospinning precursor solution was sucked into the syringe of the electrospinning equipment, and the polyacrylonitrile nanofiber material was obtained by using the electrospinning technology. Electrospinning conditions: The stainless steel nozzle model is G20, the collector is a stainless steel roller, the roller speed is 100r / min; the voltage between the nozzle and the roller is 20kV; the distance between the nozzle and the roller is 12cm; the spinning temperature is 25℃; the spinning humidity is 30%RH; the push speed is 30μL / min, and 24mL of the precursor solution is spun.

[0050] 3) The obtained polyacrylonitrile nanofiber material was flattened with a corundum plate and placed in a tube furnace for pre-oxidation treatment, that is, in an air atmosphere, the temperature was raised to 180°C at a heating rate of 2°C / min, and kept warm for 10 minutes, and then the temperature was raised to 290°C at a heating rate of 1°C / min, and kept warm for 60 minutes. Then a carbonization treatment was performed, that is, in a N2 atmosphere, the temperature was raised to 1000°C at a heating rate of 5°C / min, and kept warm for 120 minutes, and then cooled to room temperature to obtain a polyacrylonitrile carbon nanofiber electrode material, labeled as PAN-ECNFs.

[0051] The SEM images of the obtained PAN-ECNFs are shown in Figure 1 As shown in (a), the diameter of PAN coarse fibers is about 150 to 300 nm and the surface is smooth.

[0052] (II) Electrospun carbon nanofiber materials prepared from PILs-PAN mixed precursors

[0053] The preparation method comprises the following steps:

[0054] 1) Dried polyacrylonitrile (PAN) powder with a molecular weight of 150,000 was dissolved in N,N,-dimethylformamide (DMF) solution, and magnetically stirred at 80° C. for 6 h until completely dissolved, to obtain a PAN / DMF electrospinning precursor solution with a polyacrylonitrile (PAN) mass percentage concentration of 14%.

[0055] 2) 5.0g ViEtIm + Br -and 0.1 g AIBN were added to 50 mL of CHCl3 solvent, refluxed in an oil bath at 70°C for 5 h under N2 protective atmosphere, and after cooling to room temperature, the obtained product was washed with CHCl3 for 3 to 5 times and vacuum dried to obtain a light yellow solid polymeric ionic liquid (PILs).

[0056] 3) Adding polymerized ionic liquids (PILs) to the above 14% PAN / DMF electrospinning precursor solution, wherein the mass ratio of PILs to PAN is 1:100, and mixing them evenly by ultrasonic stirring to obtain a PILs-PAN mixed precursor solution.

[0057] 4) 10 mL of the PILs-PAN mixed precursor solution was sucked into the syringe of the electrospinning equipment, and continuous electrospinning was performed using the electrospinning technology to obtain binary nanofiber materials. Electrospinning conditions: the stainless steel nozzle model is G20, the collector is a stainless steel roller, the roller speed is 100 r / min; the voltage between the nozzle and the roller is 20 kV; the distance between the nozzle and the roller is 12 cm; the spinning temperature is 25 ° C; the spinning humidity is 30% RH; the push speed is 30 μL / min.

[0058] 5) The obtained binary nanofiber material was flattened with a corundum plate and placed in a tube furnace for pre-oxidation treatment, that is, in an air atmosphere, the temperature was raised to 180°C at a heating rate of 2°C / min, and the temperature was kept for 10 minutes, and then the temperature was raised to 290°C at a heating rate of 1°C / min, and the temperature was kept for 60 minutes. Then, a carbonization treatment was performed, that is, in a N2 atmosphere, the temperature was raised to 1000°C at a heating rate of 5°C / min, and the temperature was kept for 120 minutes, and then cooled to room temperature to obtain electrospun carbon nanofibers, which were labeled as PILs-PAN-ECNFs.

[0059] The thickness of the obtained PILs-PAN-ECNFs is about 50 μm, and the SEM image is as follows: Figure 1 As shown in (b), there are two types of fibers with different diameters in the material. PAN forms PAN coarse fibers with a diameter of about 100 to 300 nm, and PILs forms PILs fine fibers with a diameter of about 10 to 30 nm. The PILs fine fibers are evenly distributed on the surface of the PAN coarse fibers.

[0060] Example 2 Electrochemical performance test of electrospun carbon nanofiber electrode material prepared from PILs-PAN mixed precursor 1) Cyclic voltammetry test

[0061] Method: A three-electrode system was used, with 1 cm prepared in Example 1. 2PAN-ECNFs electrode material and PILs-PAN-ECNFs electrode material were used as working electrode, saturated glycan common electrode as reference electrode, platinum sheet as counter electrode, 0.1M VOSO4+2.0M H2SO4 as electrolyte, and the electrochemical properties of the electrodes were investigated by cyclic voltammetry with a scan rate of 5mV / s.

[0062] like Figure 2 As shown, both electrodes show V 2+ / V 3+ and VO 2+ / VO2 + However, compared with blank PAN-ECNFs, the CV curve measured on the PILs-PAN-ECNFs electrode has a larger peak current and a smaller peak potential difference, which is attributed to the larger specific surface area and better electrolyte permeability of the PILs-PAN-ECNFs electrode material, which increases the effective reaction area and improves the electrochemical reaction activity.

[0063] Finally, it should be noted that the above specific implementation methods are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.

Claims

1. An electrospun carbon nanofiber material prepared from a PILs-PAN mixed precursor, characterized in that: The PILs-PAN mixed precursor is first subjected to electrospinning technology to prepare a binary nanofiber material, and then subjected to pre-oxidation and carbonization treatment to obtain an electrospun carbon nanofiber material with a gradient pore structure; The binary nanofiber material is composed of polymerized ionic liquid PILs fine fibers uniformly distributed on the surface of polyacrylonitrile PAN coarse fibers.

2. The electrospun carbon nanofiber material prepared from a PILs-PAN mixed precursor according to claim 1, characterized in that: The diameter of the polymerized ionic liquid PILs fine fiber is 10-30 nm, and the diameter of the polyacrylonitrile PAN coarse fiber is 100-300 nm.

3. The electrospun carbon nanofiber material prepared from a PILs-PAN mixed precursor according to claim 1, characterized in that: The polymeric ionic liquids PILs are polymeric ionic liquids PILs prepared using 1-vinyl-3-methylimidazole as a monomer.

4. The electrospun carbon nanofiber material prepared from a PILs-PAN mixed precursor according to claim 1, characterized in that: The molecular weight of the polyacrylonitrile PAN is 90,000 to 150,000.

5. The method for preparing an electrospun carbon nanofiber material prepared from a PILs-PAN mixed precursor according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: 1) dissolving polyacrylonitrile (PAN) in N,N,-dimethylformamide (DMF) solution to obtain a PAN / DMF electrospinning precursor solution having a PAN mass percentage concentration of 10-20%; 2) Using 1-vinyl-3-methylimidazole as a monomer, polymeric ionic liquids (PILs) were prepared; 3) adding the polymerized ionic liquid PILs to the PAN / DMF electrospinning precursor solution prepared in step 1), mixing them evenly, and preparing a PILs-PAN / DMF mixed precursor solution; 4) The PILs-PAN / DMF mixed precursor solution is sucked into an electrospinning syringe, and electrospinning is performed using an electrospinning technique to prepare a binary nanofiber material in which polymerized ionic liquid PILs fine fibers are uniformly distributed on the surface of polyacrylonitrile PAN coarse fibers; 5) The binary nanofiber material is flattened with a corundum plate, placed in a tube furnace for pre-oxidation treatment and carbonization treatment, and then cooled to room temperature to obtain an electrospun carbon nanofiber material with a gradient pore structure.

6. The preparation method according to claim 5, characterized in that: Step 2) is specifically as follows: 1-vinyl-3-methylimidazolium bromide and azobisisobutyronitrile are added to CHCl3 solvent, refluxed in an oil bath at 70°C to 80°C for 5 to 6 hours under a N2 protective atmosphere, cooled to room temperature, and the obtained product is washed with CHCl3 and dried in vacuo to obtain polymeric ionic liquids PILs.

7. The preparation method according to claim 5, characterized in that: In step 3), the mass ratio of polymerized ionic liquid PILs:PAN is 1:50 to 1:

200.

8. The preparation method according to claim 5, characterized in that: In step 4), the process conditions of the electrospinning technology are as follows: the stainless steel nozzle model is G15~G22; the wire collector is a stainless steel roller, and the roller speed is 50~150r / min; the voltage between the nozzle and the roller is 18~22kV; the distance between the nozzle and the roller is 10~15cm; the spinning temperature is 25~30℃; the spinning humidity is 30~50%RH; the pushing speed is 10~50μL / min.

9. The preparation method according to claim 5, characterized in that: In step 5), the conditions for the pre-oxidation treatment are: in an air atmosphere, heating to 180-200°C at a heating rate of 2-5°C / min, keeping warm for 10-20 minutes, then heating to 290-300°C at a heating rate of 1-2°C / min, and keeping warm for 60-70 minutes; the conditions for the carbonization treatment are: in a nitrogen or argon atmosphere, heating to 1000-1100°C at a heating rate of 5-10°C / min, and keeping warm for 120-130 minutes.

10. Use of the electrospun carbon nanofiber material prepared from the PILs-PAN mixed precursor according to any one of claims 1 to 4 as an electrode material in an all-vanadium liquid flow battery.

Citation Information

Patent Citations

  • Transition metal phosphide nanosheet coated carbon nanofiber composite material as well as preparation method and application thereof

    CN117059404A

  • Processes for producing carbon fiber, the filament thereof, and pre-oxidized fiber

    US20120027944A1